2014
DOI: 10.2337/dc13-2106
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Short Leukocyte Telomere Length, Endotoxemia, and Severe Periodontitis in People With Diabetes: A Cross-Sectional Survey

Abstract: OBJECTIVEShortened leukocyte telomere length (LTL) and diagnosis of periodontitis are associated with an increased risk of complications and mortality in diabetes. This study investigated the association between LTL, endotoxemia, and severity of periodontitis in a large cohort of people with diabetes. RESEARCH DESIGN AND METHODSSix hundred thirty individuals (371 with type 2 and 259 with type 1 diabetes) were recruited from the University College Hospital in London, U.K. During a baseline visit, blood was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Third, in diabetic patients, there is a negative correlation between the degree of endotoxemia and the length of the telomeres in circulating leukocytes (30). Finally, in hemodialysis patients (a patient population frequently characterized by septic episodes and/or systemic inflammatory responses), telomere shortening has been reported in circulating leukocytes (31).…”
Section: Discussionmentioning
confidence: 99%
“…Third, in diabetic patients, there is a negative correlation between the degree of endotoxemia and the length of the telomeres in circulating leukocytes (30). Finally, in hemodialysis patients (a patient population frequently characterized by septic episodes and/or systemic inflammatory responses), telomere shortening has been reported in circulating leukocytes (31).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its relationship with vascular complications, telomere shortening was recently shown to be associated with depression and periodontitis, which are now recognized as new complications of diabetes.…”
Section: Telomere Attrition In Relation To Mortality and Diabetic Commentioning
confidence: 99%
“…29 Cross-sectional studies of T2DM patients showed that those with previous myocardial infarction or atherosclerotic plaques detected by carotid artery ultrasonography had a more markedly reduced LTL than those without either. 20,30 Besides its relationship with vascular complications, telomere shortening was recently shown to be associated with depression 31 and periodontitis, 32 which are now recognized as new complications of diabetes.…”
Section: Telomere Attrition In Relation To Mortality and Diabetic Commentioning
confidence: 99%
“…According to a recent study, Dental examinations characterized the levels of periodontitis and LTL was measured by PCR after DNA Extraction. Patients with periodontitis demonstrated shorter LTL (P=0.04) in those with a higher prevalence of Type 2 Diabetes (29). Shortened LTL may also be used as a forthcoming measure in those with periodontitis who may or will develop Type 2 Diabetes.…”
Section: The Effect Of Oxidative Stress Shortened Leukocyte Telomerementioning
confidence: 98%